Epididymis response partly compensates for spermatozoa oxidative defects in snGPx4 and GPx5 double mutant mice. - Anaïs Noblanc; Manon Peltier; Christelle Damon-Soubeyrand; Nicolas Kerchkove; Eléonore Chabory; Patrick Vernet; Fabrice Saez; Rémi Cadet; Laurent Janny; Hanae Pons-Rejraji; Marcus Conrad; Joël R Drevet; et al. (PLoS ONE, 2012)
We report here that spermatozoa of mice lacking both the sperm nucleus glutathione peroxidase 4 (snGPx4) and the epididymal glutathione peroxidase 5 (GPx5) activities display sperm nucleus structural abnormalities including delayed and defective nuclear compaction, nuclear instability and DNA damage. We show that to counteract the GPx activity losses, the epididymis of the double KO animals mounted an antioxydant response resulting in a strong increase in the global H(2)O(2)-scavenger activity especially in the cauda epididymis. Quantitative RT-PCR data show that together with the up-regulation of epididymal scavengers (of the thioredoxin/peroxiredoxin system as well as glutathione-S-transferases) the epididymis of double mutant animals increased the expression of several disulfide isomerases in an attempt to recover normal disulfide-bridging activity. Despite these compensatory mechanisms cauda-stored spermatozoa of double mutant animals show high levels of DNA oxidation, increased fragmentation and greater susceptibility to nuclear decondensation. Nevertheless, the enzymatic epididymal salvage response is sufficient to maintain full fertility of double KO males whatever their age, crossed with young WT female mice.